Katrina Owen: capstone - Owen, Katrina, artist (Colorado State University. Libraries, 2017)
The artist's statement: As a graphic designer, my work has to speak not only to me visually but to my viewers as well. It speaks on a simple level that appeals to all as well as to clients. I create designs that are minimal yet appealing. Before starting any piece, I research as much as I can before I do any initially sketching. Once I have enough research completed, I draft any ideas that come to mind, which helps solidify my ideas on a computer screen. I began at a young age learning how to code websites on my own. Gradually, I fell in love with the graphic elements that go into web design and everything else we see in the world today. As I work, I find inspiration everywhere whether that be from the internet, the world around me, or by traveling. Other inspirations are various graphic designers, web designers, or creative artists. One of my favorite graphic designers is Paula Scher. She is an inspiration to me because she is a female American graphic designer that has created well known logos such as, Windows 8, CNN, and Tiffany and Co. Scher has a beautiful and simplistic style that I seek to emulate. For each project, I use different mediums and materials. However, my end result priorities of keeping it simple. I do a variety of work such as, corporate identities, posters, and magazine layouts. I use programs like Adobe Illustrator, InDesign, and Photoshop. Additionally, I am also familiar with web design such as, HTML and CSS. These programs help my design projects come together in the end.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design